(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
Processes of globalization get primarity on regulations of the worlds affaires. Controversies and revivals from the periods of Cold war. remains behind antagonisms who led toward series of wars and conflicts through the world. Periods fulfillments of oscillations with peace and war, pointed at that globalization process and war how sociable phenomenon are not seen lake separated issues. The world composed of countries „classified“ how countries from First. Second or Third world is difficult to find common peaceful solution. „Double standards“ promoted by globalization always remains possibility of ne w co 11 i s i on between, ,po wer , lights“ and, interests ‘ ‘ on states and international organizations.